Oil droplets and solid particles removal using circular separator with inclined coalescence mediums : comparison between co-current and counter-current flow - Law, Puong Ling; Ngu, Lock Hei; Wong, Kien Kuok; Yusof, A. A.R (IWA Publishing, 2010)
This research investigated the effects of co- and counter-current flow patterns on oil-water-solid separation efficiencies of a circular separator with inclined coalescence mediums. Oil-water-solid separations were tested at different influent concentrations and flowrates. Removal efficiencies increased as influent flowrate decreased, and their correlationship can be represented by power equations. These equations were used to predict the required flowrate, Qss50, for a given influent suspended solids concentration Ciss to achieve the desired effluent suspended solids concentration, Cess of 50 mg/L, to meet environmental discharge requirements. The circular separator with counter-current flow was found to attend removal efficiencies relatively higher as compared to the co-current flow. As compared with co-current flow, counter-current flow Qss50 was approximately 1.65 times higher than co-current flow. It also recorded 13.16% higher oil removal at influent oil concentration, Cio of 100 mg/L, and approximately 5.89% higher TSS removal at all influent flowrates. Counter-current flow’s better removal performances were due to its higher coalescing area and constant interval between coalescence plate layers.